Conifers but not angiosperms exhibit vulnerability segmentation between leaves and branches in a temperate forest. (15th October 2018) - Jin, Ying; Wang, Chuankuan; Zhou, Zhenghu
Abstract: Vulnerability segmentation (VS), an important mechanism for protecting plants from drought, hypothesizes that the distal organs of a plant should be more susceptible to embolism than the basal organs. However, experimental studies testing the VS hypothesis for trees are limited and have reached inconsistent conclusions. Here, we tested the VS hypothesis with three angiosperms and four conifers co-existing in a temperate forest in northeastern China. The results showed that the difference in vulnerability to cavitation between leaves and branches ( P 50leaf–branch ) was positive for the conifers but negative for the angiosperms, implying that the conifers rather than the angiosperms exhibited VS. The conifers had lower leaf hydraulic safety margins and more embolism-resistant branches than the angiosperms. Although the angiosperms did not display VS, they took a hydraulic compensatory strategy (e.g., great leaf and branch hydraulic conductivities) to maintain the water supply of their leaves. In addition, we found a significant trade-off between the sapwood-specific hydraulic conductivity ( K SS ) and xylem pressure inducing 50% loss of hydraulic conductivity ( P 50branch ) across all species. Both K SS and P 50branch increased with the area-based light-saturated photosynthetic rate ( A area ), suggesting that increased embolism resistance of branches comes at the cost of reduced hydraulic efficiency, which in turn constrains the photosynthesis. A area was negatively correlated with P 50leaf–branch, further indicating that the conifers had strong VS and were associated with a conservative strategy. Conversely, the angiosperms displayed an acquisitive strategy, tending to have higher A area, leaf and branch hydraulic conductivities, but lower embolism resistance. These differentiations in the functional traits between the angiosperms and conifers provide potential mechanisms for their co-existence in this temperate forest community.